The management competencies of the directors of youth centres and indoor facilities in the municipalities - Tripolitsioti, A.; Moudakis, K.; Konstantinakos, P.; Theodorikakos, P. (Biology of Exercise, 2007)
The purpose of this study was to construct a valid and reliable instrument to determine the competencies needed to manage the health & fitness clubs and indoor facilities of Youth & Sport Organizations in the Greek Municipalities. For the purposes of the study we used (with permission) the competencies of sport managers instrument constructed by Dr KL Toh. This questionnaire comprised 96 competency statements translated into Greek with reverse translation. Following standard procedures and with the help of five academic experts from Greece, six directors of the health & fitness clubs and indoor facilities of Youth & Sport Organizations of the municipalities constructed the final version of the questionnaire, comprising 72 questions. The instrument was then administered to a sample of 101 managers. Results analysis of the internal validity revealed that the Cronbach`s alpha was 0.95. Exploratory factor analysis revealed eight factors comprising 69 competency statements: management techniques (15 items), sport science, (13 items), event management (10 items), public relations (8 items), computer skills/research (8 items), facilities management (5 items), governance (5 items), and safety/injury prevention (5 items). Further internal consistency of each factor revealed Cronbach`s alpha coefficients from 0.76 to 0.97. It is concluded that the questionnaire developed in this study is a reliable and valid instrument to measure the competencies of the managers of health & fitness clubs and indoor facilities.